Suicidal symptoms among elderly patients attending out- patient department of Tribhuvan University Teaching Hospital - Khattri, JBK; Nepal, MK (Journal of Institute of Medicine Nepal, 2007)
Background: Despite the fact that suicide and its prevention continues to be a priority area for health care, suicide in the elderly remains a neglected subject receiving little interest and research attention. Suicide rates increase with age and are very high among those 65 years and older and is the major public health problem. The aim of the study is to estimate the prevalence of suicidal symptoms among geriatric patients attending outpatient departments of Tribhuvan University Teaching Hospital in Nepal. Methods: A study group of 100 elderly patients aged 65 years and above were randomly selected from the psychiatry, medicine and general practice outpatient departments of Tribhuvan University Teaching Hospital. The symptoms of the patients were recorded carefully according to the suicidal symptoms of Hamilton Depression Rating Scale (HDRS). Results: Sixteen percent of the samples were found to experience suicidal symptoms, out of which three percents were found to attempted suicide. Conclusions: The results show very high rates of suicidal symptoms among the elderly population attending the outpatient departments. The early detection of suicidal feelings could lower the rates of suicide attempts among the elderly in the Nepalese population. It also calls for the need to strengthen the consultation psychiatry service for early intervention in the patients with suicide. Key words: Suicidal symptoms, HDRS, Depression. The full text of this paper is available at Journal of Institute of Medicine website